Circulating Small Extracellular Vesicles Profiling and Thrombin Generation as Potential Markers of Thrombotic Risk in Glioma Patients - Olga Melnichnikova; Yulia Zhilenkova; Olga Sirotkina; Ekaterina Zolotova; Konstantin Pishchulov; Malik Tastanbekov; Artem Paltsev; Maria Simakova (Frontiers in Cardiovascular Medicine, 2022)
IntroductionPatients with glioma (GM) are at a high risk of venous thromboembolism (VTE). The role of microvesiculation in the cancer-associated thrombosis mechanisms has been previously demonstrated. This study aimed to evaluate the relative abundance of extracellular vesicles (EVs) and thrombin generation (TG) in combination with standard laboratory tests in patients with newly diagnosed GM as potential prognostic markers in VTE.Materials and MethodsIn the present study, 11 patients with newly diagnosed GM and 10 healthy volunteers were analyzed. EVs were counted and their cellular origin was determined (CytoFlex B4-R2-V2, Beckman Coulter, United States), as well as thrombin generation test (TGT) (Diagnostica Stago SAS, France) was performed.ResultsIn patients with GM, the relative abundance of the CD41 + EVs (platelet-derived)—and CD105 + EVs (endothelial-derived) was significantly higher than in the control group (44.3 [40.5; 52.4] vs. 27.2 [22.9; 31.0]%, p = 0.002, and 5.4 [4.8; 7.8] vs. 1.9 [1.5; 2.8]%, p = 0.0003, respectively). The D-dimer level was higher in patients with GM compared with the control group (0.46 [0.38; 1.85] vs. 0.36 [0.27; 0.40] μg/ml FEU, p = 0.03, respectively). There was a trend toward an increase in the peak thrombin and velocity index (VI) in the GM group (p = 0.06). During the follow-up period, two patients (18%) developed thrombosis, had tumor sizes of more than 5 cm, thrombocytopenia, increased VI, and D-dimer.ConclusionAnalysis of platelet-derived EVs, platelet count, and TGT in combination with D-dimer assessment could improve the stratification of patients prone to VTE, which needs to be confirmed in a larger sample.